VISUAL EVOKED POTENTIAL IN NON-INSULIN DEPENDENT DIABETES MELLITUS PATIENTS WITHOUT DIABETIC RETINOPATHY - Nawaz Cheema; Saba Anwar; Erum Ehsan (Journal of University Medical & Dental College, 2017)
Purpose: Diabetes mellitus has multiple complications involving many organs like eyes, brain, heart and kidneys ets. In visual complications retinopathies and neuropathies are most important. Visual evoked potentials (VEPs) is used to find subclinical involvement of visual pathways in type 2 diabetics without retinopathy and comparison of visual evoked potentials (VEP) with non diabetic control subjects. Material and Methods: This study was conducted over a period of 6 months from 1st January 2016 to 30 June 2016 in ophthalmology department of Islam medical college teaching hospital Sialkot. Both male and female diabetic patients with good glycemic control and control subjects of 40-60 years of age were included. Neurostar modelec 92B equipment was used to record visual evoked potentials (VEPs) by pattern reversal stimulations and their glucose level was estimated by glucose oxidase method. Results: VEP recordings of diabetic patients showed that P100 latency was highly significantly prolonged (P<0.01) as compared to control subjects. The prolonged P100 latency is indicative of sub clinical involvement of visual pathway as compared to control subjects. In this study the correlation between P100 latency of visual evoked potentials (VEPs) and duration of disease was highly significant and subclinical involvement of visual pathways was present in 30%. Conclusion: It is an objective sensitive and non-invasive technique to detect subclinical involvement of visual pathways which is important in early detection of diabetic compilactions concerned with vision. Prolongation of visual evoked potentials (VEPs) particular P100 latency showed subclinical involvement of visual pathway in diabetic patients